The Effect of Participating in Recreational Dance Activities on the Social Skills of 10 to 12-Year-Old Children - Tsounis-Tzitzikas, Konstantinos; Goulimaris, Dimitris; Antoniou, Panagiotis; Yfantidou, Georgia; Bebetsos, Evagelos (IJRDO- Journal of Educational Research, 2019)
Developing social skills is important for people’s social life, especially for children who are at a sensitive stage of life. The aim of the study is to investigate to which extend participating in recreational dance activities effect children’s development of social skills. The participants of the research were 168 children (84 boys and 84 girls) with no previous dance experience. The experimental group, which consisted of 90 children, took up folk dance lessons in a society. The rest 78 children, who formed the control group, did not take up any regular physical activity. The data collection was made with the School Social Behavior Scale (SSBS - Merrell, 1993). The researchers examined the changes of the dimensions ‘cooperating skills’, ‘empathy’, ‘impulsivity’ and ‘disruptiveness’. Two measurements conducted (initial and final) within four months. Two-Way analysis of variance (ANOVA) with repeated measures was conducted to evaluate whether there were significant differences between the two groups and between the measurements for each dimension of the scale. The results showed that the children of the experimental group improved their social skills, contrary to the children of the control group. More specifically, there was an increase in the positive dimensions that were examined (cooperating skills, empathy) and a reduction in the negative dimensions (impulsivity, disruptiveness). Consequently, participating in learning dance activities can develop social skills, in a positive way.